Protecting Freedom of Expression in Multicultural Societies: Comparing Constitutionalism in Indonesia and Canada - Herlambang Perdana Wiratraman; Sébastien Lafrance (Universitas Airlangga, 2021)
This paper explores the similarities and differences in Indonesia and Canada regarding the constitutionally protected freedom of expression. While one may expect that both countries do not have much in common from a general standpoint, both do have several similarities in their approach to the interpretation and application of that freedom. The exercise of freedom of expression is also examined through the spectrum of jurisprudential examples from both countries, more specifically in the context of ‘hate speech’, ‘artistic expression’ and ‘language expression’.In addition, the social reality of both countries underlying the freedom of expression is uncovered. Further, the limitations imposed in both countries on that fundamental freedom are also discussed. Learning from the exercise that consisted in this paper to compare relevant laws of two countries, and despite the differences between their respective legal traditions, this study argues that freedom of expression, in two different countries such as Indonesia and Canada, can play a more effective role in a society with a multicultural character that complies with the rule of law.